Cone beam CT as an aid to diagnosing mixed radiopaque radiolucent lesions in the mandibular incisor region - Krishnan, Unni (BMJ Case Rep, 2015)
We present two cases where the identities of mixed radiopaque radiolucent lesions in the lower incisor region were unclear, although the position of the lesions and positive pulp sensitivity tests were suggestive of periapical osseous dysplasia. In the first case, the lesion presented as a solitary round mixed radiopaque radiolucent periapical lesion, suggestive in some images as periapical osseous dysplasia. Cone beam CT (CBCT) provided clear images, which confirmed the diagnosis and, additionally, the images showed evidence of initial lesions associated with other anterior teeth and some destruction of the labial plate, not evident on the conventional radiographs. In the second case, radiopacities were identified within the lesion on conventional radiographs, but CBCT imaging also showed extensive and unexpected perforation of the lingual plate. Such destruction of cortical plates may be a feature of periapical osseous dysplasia, which is not visible in conventional radiography.